Peningkatan Kompetensi dan Kreativitas Wirausaha Menuju Peningkatan Jumlah Ekspor pada UMKM Kota Depok melalui Program Capacity Building - Vivi Iswanti Nursyirwan; Sasmita Sari Ardaninggar (Jurnal PKM Manajemen Bisnis, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting the national economy. However, low competitiveness and limited export capabilities are major challenges in Indonesia, including in Depok City. This program aims to improve entrepreneurial competence and creativity through capacity building, enabling Depok MSMEs to penetrate the export market. The implementation method uses a participatory action research (PAR) approach through training on entrepreneurial competence and creativity related to exports. The PKM was held on December 7, 2025. There were 39 active participants during the PKM event. The resulting outputs were increased entrepreneurial competence and creativity, cognitively and skill-wise, among fostered partners, as well as an increase in digital export literacy from 55% before the PKM event to 80%. The results of the PKM participant questionnaire indicated that participants benefited from this PKM event and expressed their desire for future PKM implementations to be well-received in terms of MSME development from a technological perspective.